Esthesioneuroblastoma: the impact of brain oncological disease on neuropsychological changes – Clinical Case Study - Da Silva Rodrigues, Charles Ysaacc (Interacciones, 2022)
Background: Esthesioneuroblastoma-type brain oncology is a rare tumor, but with extensions that can reach the base of the skull and, occasionally, can present long-distance metastases that commonly reach the lungs. We aimed to identify and analyze the neuropsychological changes before and after the surgical intervention. Methods: Only one participant was considered for this case study, a 53-year-old man who lived in the city of Lisbon. A screening consisting of various subtests of the WISC and the complex figure of Rey was applied. In addition, we used the EADS test to assess emotional regulation. Results: In the preoperative evaluation, significant alterations were verified for attention, memory, executive functions and all areas of emotional regulation. Once the tumor was removed, hardly any alterations were verified in executive functions and depressive symptomatology. Conclusions: Significant improvements are verified due to natural stimulation, however, executive functions will have to follow a neuropsychological rehabilitation program to minimize the damage.